Contribution of Minimally Invasive Bone Augmentation With PMMA Cement in Primary Fixation of Schatzker Type II Tibial Plateau Fractures - Vendeuvre, T.; Koneazny, C.; Brèque, C.; Rigoard, P.; Severyns, M.; Germaneau, A. (Frontiers in Bioengineering and Biotechnology, 2022)
Background: The most common type of fracture of the lateral tibial plateau is the Schatzker type II split-depressed fracture. Minimally invasive surgery using balloon reduction appears to be very promising compared to the gold standard using a bone tamp. This surgery aims to have the best reduction and stabilization to benefit from an early passive and active rehabilitation to avoid stiffening and muscle wasting. Using a balloon for fracture reduction has allowed the use of semi-liquid Injectable Bone Cement (IBC) fillers. These fillers can be phosphocalcic or polymethyl methacrylate (PMMA). The latest recommendations on these IBCs in spinal surgery increasingly rule out phosphocalcic fillers because of their low mechanical strength. Questions/purposes: 1) What is the mechanical influence of IBC filling (PMMA) regarding the split and depression components of a Schatzker type II fracture? 2) What is the mechanical influence of osteosynthesis regarding the split and depression components of a Schatzker type II fracture with or without PMMA filing in three different kinds of percutaneous fixations? Methods: This biomechanical study was performed on 36 fresh frozen tibia/fibula specimens. Six groups were formed according to the type of percutaneous osteosynthesis or possible PMMA filling. Mechanical strength tests were carried out using a Unicompartmental Knee prosthesis and displacement components were measured on either side of the separation on the anterolateral facet by optical method. Results: We found a significant difference between cementless and cemented osteosynthesis for depression fracture stabilization (difference −507.56N with 95% confidence interval [−904.17; −110.94] (p-value = 0.026)). The differences between the different types of osteosynthesis were not significant (p-value = 0.58). There was a significant difference between osteosynthesis without cement and osteosynthesis with cement on separation (difference −477.72N [−878.52; −76.93] (p-value = 0.03)). The differences between the different types of fixations were not significant regarding separation (p-value = 0.99). Conclusion: PMMA cement significantly improves primary stability, regardless of the type of osteosynthesis for a Schatzker type II plateau fracture. Filling with PMMA cement during tuberoplasty seems to be a very promising strategy in association with percutaneous osteosynthesis to allow rapid recovery after surgery.